Assessing Effectiveness of a Chiropractic Adjustment for an Individual Patient: A Case Study in Methodology - John Hart, DC, MHSc (International Journal of Innovative Research in Medical Science, 2021)
Effectiveness of an intervention can be assessed at the level of the individual patient by comparing instances of progress with the intervention versus instances of progress where the intervention was not used. This case report presents a method used for such determination for an individual chiropractic patient.